A 20-year analysis of reported food fraud in the global beef supply chain. (October 2020) - Robson, Kelsey; Dean, Moira; Brooks, Stephanie; Haughey, Simon; Elliott, Christopher
Abstract: Background: The Horsemeat Scandal of 2013 highlighted vulnerabilities within the European beef supply chain. The report resulted in mass product recalls across Europe, a downturn in beef sales, and subsequent economic losses for genuine actors in the supply chain. The aim of this review was to improve understanding of beef supply chain vulnerability via the use of trend analysis, to enable the formulation of strategies that may help in the prevention and detection of fraud in beef products, and facilitate greater protection for consumers and industry in the future. Scope and approach: Relevant Food notifications published in the Rapid Alert System for Food and Feed (RASFF) and HorizonScan in 1997–2017 were extracted and analysed to determine their overall pattern. Frauds/adulterations were categorized by the type of fraud, their location in the food production chain, the notifying country and the origin of the food. Conclusions: Counterfeiting was the most common type of fraud in the beef industry; it accounted for 42.9% of all reports documented. When reports were classified by area in the supply chain in the report occurred, 36.4% of all cases were attributed to primary processing, of which 95.5% were counterfeiting cases. Counterfeiting included products manufactured/packed on unapproved premises, or without appropriate inspection or documentation, as well as products issued with fraudulent health certificates. Thus we conclude counterfeit product was found to be the biggest threat to the beef supply chain in relation to fraud type. Highlights: 413 fraud reports in the beef supply chain were identified between 1997 and 2017. Counterfeiting accounted for 42.9% of identified fraud. Primary processing is the most vulnerable area, accounting for 35.8% of reports.